Comparative Pharmacokinetics and Local Tolerance of Tenofovir Alafenamide (TAF) From Subcutaneous Implant in Rabbits, Dogs, and Macaques - Gatto, G. J.; Krovi, A.; Li, L.; Massud, I.; Holder, A.; Gary, J.; Mills, P.; Mitchell, J.; Luecke, E.; Demkovich, Z. R.; Heneine, W.; García-Lerma, J. G.; et al. (Frontiers in Pharmacology, 2022)
The administration of antiretrovirals (ARVs) for HIV pre-exposure prophylaxis (PrEP) is highly efficacious and may benefit from new long-acting (LA) drug delivery approaches. This paper describes a subcutaneous, reservoir-style implant for the LA delivery of tenofovir alafenamide (TAF) and documents the preclinical assessment of implant safety and pharmacokinetics (PKs) in New Zealand White (NZW) rabbits (3 groups of n=5), beagle dogs (2 groups of n=6), and rhesus macaques (2 groups of n=3). Placebo implants were placed in rabbits (n=10) and dogs (n=12). Implant parameters, including selection of the ionic form of TAF, choice of excipient, and PCL formulation were tuned to achieve targeted concentrations of the active anabolite of TAF, tenofovir diphosphate (TFV-DP), within peripheral blood mononuclear cells (PBMCs) and mucosal tissues relevant to HIV transmission. Sustained concentrations of TFV-DP in PBMCs over 100 fmol/10^6 cells were achieved in all animal species indicating that the implants effectively delivered TAF for 3-6 months. Unlike placebo implants without TAF, all active implants resulted in local adverse events (AEs) proximal to the implant ranging in severity from mild to moderate and included dermal inflammation and necrosis across all species. Despite these AEs, the implant performed as designed and achieved a constant drug release profile, supporting the continued development of this drug delivery platform.